Islamic conditions for sustainable development: A case study of International Islamic School (IIS), IIUM - Amanullah, Muhammad (2013)
Different types of development are required for modern comfortable existence and improvement of all aspects of human life. Important among them are human, moral, economic, infrastructural, social, and educational developments. All these developments can be either only for present generation, or they can be for both present and future generations to come. If these developments are beneficial only for present generation but they are harmful for future generations, they are not considered to be sustainable developments. When it had been discovered that in their developmental works, some developers did not consider the welfare of the future generations and therefore these developments had been proved to be harmful for them (future generations), some governments started to impose conditions for sustainable development. One of these early governments who imposed these conditions was the government of Canada. Canadian conditions are not comprehensive. A set of comprehensive conditions for this development is yet to be developed. Islam also has conditions of sustainable development. Analyzing the related Qur’anic verses and Prophetic ahadith, this paper intends to develop a set of comprehensive conditions of sustainable development so that they will be beneficial for those governments and organizations who really want to do sustainable development for both present and future generations. Additionally, this study intends to conduct a survey to determine whether IIS building complex fulfills these conditions or not.